Assessment of socio-demographic factors, health status and the knowledge on probiotic dairy products - Lutfiye Yilmaz-Ersan; Tulay Ozcan; Arzu Akpinar-Bayizit (Food Science and Human Wellness)
The probiotic dairy products have become the fastest growing in functional foods market in response to the increasing numbers of consumers interested in improving their health. Therefore, data collected from 314 participants in the city of Bursa, Turkey, were analyzed with the aim to assess the socio-demographic characteristics and health status as well as the consumer’s knowledge and awareness of probiotic dairy products in order to gain a better understanding of consumers’ attitudes. It was observed that socio-demographic characteristics of the participants were not significantly associated with the degree of knowledge or awareness and purchasing frequencies of probiotic dairy products. Having a higher educational level, higher income level and being a woman indicated an increased the awareness, knowledge and purchase probability of probiotic dairy products. This study emphasized that consumers should be more informed about the positive relationship between a healthier life and the consumption of probiotic dairy products.